Analysis of Factors Associated with Return-to-Work After Lumbar Surgery up to 2-Years Follow-up: A Michigan Spine Surgery Improvement Collaborative (MSSIC) Study. Issue 1 (1st January 2022) - Macki, Mohamed; Anand, Sharath Kumar; Hamilton, Travis; Lim, Seokchun; Mansour, Tarek; Bazydlo, Michael; Schultz, Lonni; Abdulhak, Muwaffak M.; Khalil, Jad G.; Park, Paul; Aleem, Ilyas; Easton, Richard; et al.
Abstract : Preoperative employment, followed by private insurance, were strongest predictors of return-to-work at all three follow-up time intervals: 90 d, 1 y, and 2 y. In two independent subanalyses of only preoperatively employed patients and preoperatively unemployed patients, private insurance was the only predictor of return-to-work at all three time intervals in both subanalyses. Abstract : Study Design: Michigan Spine Surgery Improvement Collaborative (MSSIC) prospectively collects data on all patients undergoing operations for degenerative and/or deformity indications. Objective: We aimed to identify which factors are significantly associated with return-to-work after lumbar surgery at long-term follow-up. Summary of Background Data: Prior publications have created a clinically relevant predictive model for return-to-work, wherein education, gender, race, comorbidities, and preoperative symptoms increased likelihood of return-to-work at 3 months after lumbar surgery. We sought to determine if these trends 1) persisted at 1 year and 2 years postoperatively; or 2) differed among preoperatively employed versus unemployed patients. Methods: MSSIC was queried for all patients undergoing lumbar operations (2014–2019). All patients intended to return-to-work postoperatively. Patients were followed for up to 2 years postoperatively. Measures of association were calculated with multivariable generalized estimating equations. Results: Return-to-work increased from 63% (3542/5591) at 90 days postoperatively to 75% (3143/4147) at 1 year and 74% (2133/2866) at 2 years postoperatively. Following generalized estimating equations, neither clinical nor surgical variables predicted return-to-work at all three time intervals: 90 days, 1 year, and 2 years postoperatively. Only socioeconomic factors reached statistical significance at all follow-up points. Preoperative employment followed by insurance status had the greatest associations with return-to-work. In a subanalysis of patients who were preoperatively employed, insurance was the only factor with significant associations with return-to-work at all three follow-up intervals. The return-to-work rates among unemployed patients at baseline increased from 29% (455/1100) at 90 days, 44% (495/608) at 1 year, and 46% (366/426) at 2 years postoperatively. The only two significant factors associated with return-to-work at all three follow-up intervals were Medicaid, as compared with private insurance, and male gender. Conclusion: In patients inquiring about long-term return-to-work after lumbar surgery, insurance status represents the important determinant of employment status. Level of Evidence: 2